Stress Responses in Plants 2015
DOI: 10.1007/978-3-319-13368-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Signal Perception and Mechanism of Salt Toxicity/Tolerance in Photosynthetic Organisms: Cyanobacteria to Plants

Abstract: High salt concentration represents one of the most significant abiotic constraints, affecting all life forms including plants and cyanobacteria. Soil salinity curtails plant growth by way of osmotic, ionic and oxidative stresses resulting in multiple inhibitory effects on various physiological processes such as growth, photosynthesis, respiration and cellular metabolism. In order to combat high salinity, various adaptive strategies employed include ion homeostasis achieved by ion transport and compartmentaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 160 publications
(157 reference statements)
1
4
0
Order By: Relevance
“…A su cient water content is bene cial for subcellular structural stabilization and cell recovery from stress. Waterlogging often reduces plant RWC (Balakhnina 2015;Haddadi et al 2016), as demonstrated in the current study. Prolonged waterlogging reduced relative water content dramatically (Fig.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…A su cient water content is bene cial for subcellular structural stabilization and cell recovery from stress. Waterlogging often reduces plant RWC (Balakhnina 2015;Haddadi et al 2016), as demonstrated in the current study. Prolonged waterlogging reduced relative water content dramatically (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…All of these waterlogging stress-induced adaptations aid in the capture and diffusion of oxygen (Kitomi et al, 2020) Plants have mechanisms to cope with this stress in addition to the adaptations mentioned above, such as increased availability of soluble sugars, increased activity of glycolytic pathway and fermentation enzymes, and involvement of antioxidant defense mechanism to cope with post hypoxia/anoxia oxidative stress (Sairam et al 2008;Silva et al 2017). Soluble sugar acts as an osmotic agent or osmoprotector, protecting the structural integrity of proteins and membranes under abiotic circumstances (Béjaoui et al 2016;Balakhnina 2015). In fact, the quantity of stored carbohydrates and their accessibility may distinguish between tolerant and intolerant species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under salt stress, polyphosphates and orthophosphates can also assist in regulating ion homeostasis in plant cells 126 . Excessive salt can damage cells and cause oxidative stress by upsetting the equilibrium of ions inside and outside plant cells 125 .…”
Section: Discussionmentioning
confidence: 99%